헤어미용종사자의 그릿이 긍정심리자본과 경영성과에 미치는 영향: 직무만족도의 매개효과 - 최유리; Yoo-ri Choi; 이재숙; Jae-sook Lee (한국미용학회지, 2024)
This study investigates the impact of hairdressing professionals’ grit on positive psychological capital and managerial performance, with an empirical analysis of the mediating effect of job satisfaction. The study’s subjects consisted of 320 active hairdressing professionals nationwide, from whom data were collected through a structured survey. The collected data were analyzed using descriptive statistics, confirmatory factor analysis, correlation analysis, structural equation modeling, and bootstrapping for mediating effects. The conclusions derived from a series of research procedures are as follows: First, the grit of hairdressing professionals was found to have a significant positive effect on job satisfaction. Second, the grit of hairdressing professionals had a significant positive impact on positive psychological capital but showed no significant effect on managerial performance. Third, job satisfaction among hairdressing professionals was shown to have a significant positive effect on positive psychological capital and managerial performance. Fourth, job satisfaction was found to have a full mediating effect in the relationship between grit and managerial performance for hairdressing professionals. This study provides an in-depth examination of the role of grit in the successful goal achievement of hairdressing professionals, offering foundational data for establishing human resource management and managerial strategies in the hairdressing industry.